Adsorption of Na on silicene for potential anode for Na-ion batteries. (20th February 2019) - Xu, Sen; Fan, Xiaofeng; Liu, Jialin; Jiang, Qing; Zheng, Weitao; Singh, David J.
Abstract: There is a great need to develop efficient and stable anodes suitable for high performance Na ion batteries (NIBs). Here we explore the interaction between Na and silicene in context of NIB anodes with first-principles methods including molecular dynamics simulations. We find that Na ions are adsorbed on silicene mainly via the formation of Na chains based on the agglomeration of Na pairs above and below the silicene sheet around top sites. This chain-on-top model is very different from the usual mechanism of atomic adsorption on a surface, as in Li on graphene. With the increase of Na concentration up to x = 1, a phase transition happens with the formation of a new stable structure Na2 Si2 . The interaction between Na and silicene is sufficiently strong that there no tendency for formation of Na clusters indicating stability of Na/silicene anodes. Additionally, the interaction is not so strong as to lead to breaking of the silicene lattice. The capacity of Na on silicene may be more than 954 mAh/g, which implies that it has the potential to be an excellent candidate anode material.